Knowledge and attitude of teachers in selected Malaysian primary school towards dental injuries / Syazwani Hassan ...[et al.] - Hassan, Syazwani; Zulkifly, Nur Nabila; Venkiteswaran, Annapurny; Abdul Halim, Rohaida (Universiti Teknologi MARA Shah Alam, 2018)
To ascertain the level of knowledge among primary school teachers towards the management of traumatic dental injuries (TDIs) in school and to determine the preference among teachers regarding the education tools that can be used to increase awareness and knowledge among them. A total of 150 teachers from primary schools in three different districts were included in the study and they were given self-administered questionnaires to be filled. The validated questionnaire was distributed randomly in the selected schools. The questionnaire included two scenarios comprising of tooth fracture and avulsion. Questions regarding awareness and management of these scenarios were asked. All 150 participants answered the questionnaire; of these 74% were females 26% were males. 64% of the participants had received tertiary education. Although 70% of teachers had obtained first aid training, only 9.3% of them had received training regrading dental injuries. About 53% of participants knew the correct answer for the appropriate response to fractured tooth and only 35.3% managed to correctly answer the question related to appropriate response to an avulsed tooth. Only 38.7% knew about appropriate rinsing solution and a mere 4.7% were familiar with proper storage media. Even though the teachers have poor knowledge regarding management of dental injuries, it is reassuring to know that 93% of them are keen on further training and awareness. More educational programmes need to be introduced to empower the teachers with the relevant knowledge required to deal with dental emergencies.